![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : ( 12x - 5 ) ( 4x - 1 ) + ( 3x - 7 ) ( 1 -16x ) = 81
=> 48x2 - 20x - 12x + 5 + 3x - 7 - 48x2 + 112x = 81
=> 80x - 2 = 81
=> 80x = 83
=> x = 83/80
![](https://rs.olm.vn/images/avt/0.png?1311)
( 12x - 5 ) ( 4x -1 ) + ( 3x - 7 ) ( 1 - 16x ) = 81
48x2-12x-20x+5+3x-48x2-7+112x=81
83x-2=81
83x=83
x=1
Vậy x=1
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\Leftrightarrow48x^2-12x-20x+5+3x-48x^2-7+112x=81\)
\(\Leftrightarrow-32x+115x=81+2\)
\(\Leftrightarrow83x=83\)
\(\Leftrightarrow x=1\)
Vậy \(x=1\)
~Chúc bạn học tốt~
![](https://rs.olm.vn/images/avt/0.png?1311)
#)Giải :
Câu 1 :
5x(1 - 2x ) - 3x ( x+18) = 0
<=> 5x - 10x^2 - 3x^2 - 54x = 0
<=> -13x^2 - 49x = 0
<=> x= 0 hoặc x = - 49/13
Vậy x có hai giá trị là 0 và - 49/13
![](https://rs.olm.vn/images/avt/0.png?1311)
(12x-5)(4x-1)+(3x-7)(1-16x)=81
48x^2-12x-20x+5+3x-48x^2-7+112x=81
83x-2=81
83x=83
x=1
(12x-5)(4x-1)+(3x-7)(1-16x)=81
12x ( 4x- 1) - 5(4x-1) + 3x(1-16x) -7(1-16x) =81
12x . 4x -12x - 20x + 5 + 3x - 3x. 16x - 7 + 7.16x = 81
48x^2 -12x - 20x + 5 + 3x - 48x^2 - 7 + 112x = 81
(48x^2 - 48x^2) + (112x - 12x - 20x +3x) - ( 7 - 5) =81
83x = 81 + 2
83x =83
x=1
ht nha bạn
![](https://rs.olm.vn/images/avt/0.png?1311)
( 12x - 5 )( 4x - 1 ) + ( 3x - 7 )( 1 - 16x ) = 81
( 12x.4x ) + ( 12x.1) + ( -5.4x) + ( -5).(-1) + 3x.1 + 3x. (-16x) + (-7).1 + ( -7 ).(-16x) = 81
\(48^2-12x-20x+5\)\(+3x-48x^2-7+112x\)\(=81\)
\(\left(-12x-20x\right)\)\(+\left(5-7\right)\)\(+\left(3x+112x\right)\)\(=81\)
\(-32x-2+115x^2\)\(=81\)
\(\left(-32x^2+115x^2\right)-2\)\(=81\)
\(83x-2\)\(=81\)
\(83x=81+2\)
\(83x=83\)
\(\Rightarrow x=1\)
( 12x - 5 )( 4x - 1 ) + ( 3x - 7 )( 1 - 16x ) = 81
<=> 48x2-32x+5 +3x-48x2-7+112x=81
<=> 83x= 81 +2
<=> 83x=83
<=> x=1
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(12x-5\right)\left(4x-1\right)+\left(3x-7\right)\left(1-16x\right)=81\)
\(\text{⇔}48x^2-32x+5-48x^2-7+115x=81\)
\(\text{⇔}83x-2=81\)
\(\text{⇔}83x=83\)
\(\text{⇔}x=1\)
Vậy: x=1
Ta có: \(\left(12x-5\right)\left(4x-1\right)+\left(3x-7\right)\left(1-16x\right)=81\)
\(\Leftrightarrow48x^2-12x-20x+5+3x-48x^2-7+112x=81\)
\(\Leftrightarrow83x=83\)
hay x=1
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(12x-5\right)\left(4x-1\right)+\left(3x-7\right)\left(1-16x\right)=81\)
\(\Leftrightarrow48x^2-32x+5+48x^2+115x-7=81\)
\(\Leftrightarrow83x=83\)
\(\Leftrightarrow x=1\)
\(\Leftrightarrow48x^2-12x-20x+5+3x-48x^2-7+112x=81\\ \Leftrightarrow83x=83\Leftrightarrow x=1\)
12x-5)(4x-1)+(3x-7)(1-16x)=81
⇒48x2−32x+5−48x2+115x−7=81
⇒48x2−32x+5−48x2+115x−7=81
⇒83x=83
⇒x=1
(12x-5)(4x-1)+(3x-7)(1-16x)=81
12x ( 4x- 1) - 5(4x-1) + 3x(1-16x) -7(1-16x) =81
12x . 4x -12x - 20x + 5 + 3x - 3x. 16x - 7 + 7.16x = 81
48x^2 -12x - 20x + 5 + 3x - 48x^2 - 7 + 112x = 81
(48x^2 - 48x^2) + (112x - 12x - 20x +3x) - ( 7 - 5) =81
83x = 81 + 2
83x =83
x=1